Management information requirements of heads of university departments : a critical success factors approach. - PELLOW, A. (1993)
Examines the problems of developing management information systems in universities, with particular attention to the information needs of Heads of Departments. Explores the potential of the Critical Success Factors Methodology for assessing information requirements.